Art in Canada - Mayer, Marc 1956- (National Gallery of Canada, 2017)
Discover the many themes and movements that have shaped Canada's visual arts landscape since 1968. Continuing the storylines from the new Canadian and Indigenous Galleries, this special exhibition invites visitors to experience more than 150 works in all media, including sculpture, painting, video art, installation, drawing and photography. From the feminist art movement of the 1970s to present-day Inuit art, the richness of the national Canadian and Indigenous contemporary art collections is on full display. Exhibition: National Gallery of Canada, Ottawa, Ontario (03.05.2017 - 06.05.2018)
Keywords: National Gallery of Canada; Geschichte; Kunst; Kanada; Art, Canadian / History; Musée des beaux-arts du Canada / Catalogues; Art canadien / Histoire / Expositions; Art, Canadian; History; Bildband; Katalog